Potential of Arthrobacter nicotiniae to Preferentially Remove Lead, Cadmium, Silver and Zinc from Contaminated Soil from Amaonye-Ishiagu Agricultural Forest, Ebonyi State, Nigeria - J. O. Etuke; N. I. Ihimekpen (Journal of Applied Sciences and Environmental Management, 2023)
This study evaluates the potential of Arthrobacter nicotiniae to preferentially remove lead, cadmium, silver and zinc from contaminated soil from Amaonye-ishiagu Agricultural Forest, Ebonyi State, Nigeria using standard methods. The study revealed optimum values of factor as 8ml of nutrient volume, 5g of the organism, 30oC of temperature, pH of 8 and stirring frequency of 4pw.  The study showed 79.78% removal of lead, 61.50% removal of cadmium, 48.59% removal of arsenic and 7.04% removal of zinc on the 35th day. The organism is thus good for lead and cadmium pollution control, arsenic pollution abatement but it is neither good for zinc pollution control, nor abatement.